2015
DOI: 10.3109/10837450.2015.1035725
|View full text |Cite
|
Sign up to set email alerts
|

Closantel nano-encapsulated polyvinyl alcohol (PVA) solutions

Abstract: The influence of closantel on the rheological and physicochemical properties (particle size and by UV-Vis absorption spectroscopy) of PVA aqueous solutions is studied here. About 1% PVA aqueous solutions were prepared by varying the closantel content. The increase of closantel content led to a reduction in the particle size of final solutions. All the solutions were buffered at pH 7.4 and exhibited shear-thinning behavior. Furthermore, in oscillatory flow, a "solid-like" type behavior was observed for the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, there are already more recent studies reporting new formulations of niclosamide, as a development of amorphous solid dispersion [ 174 ] or reformulated niclosamide as a niclosamide stearate prodrug therapeutic [ 175 ]. Moreover, similar reformulation efforts already exist in the case of other salicylanilides such as closantel [ 171 ], rafoxanide [ 170 ] and even in the case of structurally related nitazoxanide [ 172 , 176 ].…”
Section: Cancer Clinical Trials and Pharmacokinetic Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…However, there are already more recent studies reporting new formulations of niclosamide, as a development of amorphous solid dispersion [ 174 ] or reformulated niclosamide as a niclosamide stearate prodrug therapeutic [ 175 ]. Moreover, similar reformulation efforts already exist in the case of other salicylanilides such as closantel [ 171 ], rafoxanide [ 170 ] and even in the case of structurally related nitazoxanide [ 172 , 176 ].…”
Section: Cancer Clinical Trials and Pharmacokinetic Propertiesmentioning
confidence: 88%
“…In general, salicylanilides are weakly acidic, highly lipophilic compounds [ 17 ]. Low water solubility is typical not only for niclosamide [ 169 ], but also for other salicylanilides such as rafoxanide (whose solubility in water was reported to be less than 0.1 μg/mL) [ 170 ], closantel [ 171 ] and for nitrothiazolyl-salicylamide nitazoxanide as well [ 172 ]. As it was already mentioned, to overcome challenges connected to the undesirable physicochemical properties that influence oral bioavailability, a number of studies reported diverse innovative formulations of salicylanilides.…”
Section: Cancer Clinical Trials and Pharmacokinetic Propertiesmentioning
confidence: 99%
“…Due to the increase of the dipole interaction among the suspended magnetic additives, they can reversibly change the effective viscosity and modulus by forming a chain structure under an external magnetic field, showing a typical shear-thinning behavior [28]. Many groups have reported that the particles tend to form aggregates due to long-range attractions in system; subsequently the aggregates are disrupted under flow, resulting in a shear thinning behavior toward motion [29][30][31][32][33]. Chen et al [34] treated the MWNT with functionalized surfaces and controlled morphologies to form a silicon oil based rheological material.…”
Section: Introductionmentioning
confidence: 99%